Robotics: Science and Systems VIII 2012
DOI: 10.15607/rss.2012.viii.032
|View full text |Cite
|
Sign up to set email alerts
|

Practical Route Planning Under Delay Uncertainty: Stochastic Shortest Path Queries

Abstract: Abstract-We describe an algorithm for stochastic path planning and applications to route planning in the presence of traffic delays. We improve on the prior state of the art by designing, analyzing, implementing, and evaluating data structures that answer approximate stochastic shortest-path queries. For example, our data structures can be used to efficiently compute paths that maximize the probability of arriving at a destination before a given time deadline.Our main theoretical result is an algorithm that, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…It is shown that the utility function has to be either affine linear or exponential; otherwise, optimal substructure of the problem is not guaranteed. Nikolova et al [20] and Lim et al [14], [15] further extend the work and focus on stochastic road networks. In [27], Wu et al propose an approach to model risk-taking behavior based on the theory of stochastic dominance(SD), and use it to find optimal paths for different utility functions.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…It is shown that the utility function has to be either affine linear or exponential; otherwise, optimal substructure of the problem is not guaranteed. Nikolova et al [20] and Lim et al [14], [15] further extend the work and focus on stochastic road networks. In [27], Wu et al propose an approach to model risk-taking behavior based on the theory of stochastic dominance(SD), and use it to find optimal paths for different utility functions.…”
Section: Related Workmentioning
confidence: 97%
“…Most of research works done in this area use a meanrisk model [15], [21], [19] which combines the mean and variance of the travel time as a single linear objective function that needs to be optimized. Nevertheless, choosing appropriate coefficients for such a linear objective function is quite tricky and often heuristically done via experiments.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the shortest path problem with probabilistic edge weights is found in [18]. In [19] a stochastic shortest path algorithm is used to solve a route planning problem in the presence of uncertain traffic delays. [20] uses expectations of link delays to solve a network routing problem.…”
Section: Delay Tolerant Networkingmentioning
confidence: 99%
“…Existing algorithms for KShP (classical version) include a modified Bellman-Ford algorithm that stores the top K shortest paths at each pass instead of storing only the shortest (JGraphT library), and Yen's algorithm [23]. The stochastic shortest path problem (KSfP with K = 1) is a non-convex combinatorial problem [19]. A dynamic programming approach is incorrect since sub-paths of optimal paths are not optimal.…”
Section: K-safest Paths Problem (Ksfp)mentioning
confidence: 99%
“…The conventional paradigm for solving the problem is to assign weights to edges and then to sum up the weights of a path's edges to compute the cost of the path [4,10,12,21,22,25]. This conventional paradigm is inadequate in terms of accuracy and efficiency.…”
Section: Introductionmentioning
confidence: 99%